Giriraja Spent Hen Meat Patties Prepared by Using Food Processor - Reddy, B. Ramachendra; Mandal, P. K.; Kasthuri, S.; Venugopal, S.; Pal , U. K. (Journal of Meat Science, 2019)
Processing of meat from spent hen to different value added products by comminution and emulsion formation opens the avenues for its economic utilization. By using cheaper equipment like food processor we can produce meat products economically for small scale business. Among the emulsion based products, chicken patties are one of the most acceptable value added comminuted meat products. Hence, the present study was proposed to standardize procedure and the recipe to prepare patties using food processor. The standardi zation of procedure for the preparation of patties using food processor different running time (2, 3 and 4 minutes) was carried out. The recipe of patties was standardized using different levels of meat (65, 70 and 75%) and oil (7, 10 and 13%). The patties prepared with food processor by 3 minutes running time had significantly (P<0.05) higher emulsion stability. The patties prepared with 70 and 75% meat had significantly (P<0.05) better physico-chemical and sensory qualities. The patties prepared with 7 and 10% oil showed signifi cantly (P<0.05) better physico-chemical qualities and desired sensory scores. Hence, 3 minutes running time, 70% meat and 7% oil were selected for the preparation of spent hen patties using food processor.